PERANAN UNICEF DALAM MENANGANI CHILD TRAFFICKING DI INDONESIA - Nori Oktadewi (Journal of Islamic World and Politics, 2018)
Child Trafficking is part of child abuse and one of the global  issues. United Nation has established  organization special for children, the organization is UNICEF (United Nations International Children’s Emergency Fund). UNICEF defines a system to protect Children as a component of law, policy, regime and services needed in all the social sectors For Protect the children, Indonesia has ratifications Convention Right of The Children, passed on 20 November 1989, and started to have the force of law on 2 September 1990. For overcome child trafficking in Indonesia UNICEF makes a Program NPAs (National Plan of Action for the Elimination of Child).  This research is descriptive research, which is   explaining about the role of UNICEF regarding to overcome Child Trafficking especially in Indonesia. This Research aims o know how the role of UNICEF  to overcome Child Trafficking of the  children In Indonesia and what the factor has influenced child trafficking in Indonesia still high although Indonesia was cooperation with UNICEF .Presented data is secondary data which is collected from various book, article, journals, newspapers  and internet related cases.  Result of this  research show us  about child trafficking in Indonesia still high,  this matter influenced by External factors like local Government, security Agency, geographical, law institution and society (was influenced by proverty, low information and education, low pay attention by parents).   Keyword : UNICEF, Child trafficking, United Nation, NPAs,Global issues